FACTORS AFFECTING THE SATISFACTION ON MALAYSIAN HEALTH CARE SERVICES BY BANGLADESHI MIGRANT WORKERS IN SARAWAK : A CROSS-SECTIONAL EMPIRICAL STUDY - Md Mizanur, Rahman; Mohamad Taha, Arif; Razitasham, Safii; Zainab, Tambi; Cliffton, Akoi; Zulkifli, Jantan; Drend, Jores; Winnie, Johnny (Mümin POLAT, 2020)
Providing good quality health care to all inhabitants including the foreign workers is one of the Government’s health care objectives. However, information is very limited about the migrant worker’s perceived satisfaction of health care. This study aimed to assess the level of satisfaction on health care services and factors affecting it in Sarawak, Malaysia. This cross-sectional study was conducted in three districts in Kuching Division, Sarawak. A total of 314 Bangladeshi workers were interviewed by face to face interview. The level of satisfaction was measured on Likert’s scale adapted from previous studies. Data entry and analysis was done by IBM SPSS version 22.0. A p-value less than 0.05 was considered as statistically significant. The satisfaction on health care was assessed by four domains viz. technical quality, interpersonal communication, facilities and accessibility in the health care. A stepwise multinomial logistic regression analysis revealed that payment on a daily basis (p<0.001), health insurance in Sarawak and cultural behaviour appeared to be poten-tial predictors of average level of satisfaction on health care. However, no variables were identified as the predictors of good level of satisfaction. The field note analysis revealed that the quality of healthcare is better in Malaysia compared to Bangladesh, but health care is more expensive in Malaysia. This study was conducted in a very small scale; thus, the results should not be generalized. However, the findings of this study could be used as a policy guideline to develop a migrant worker's friendly health care services in the country.